2010
DOI: 10.1002/pssc.200983654
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN/GaN‐based normally‐off GaN MOSFET with stress controlled 2DEG source and drain

Abstract: AlGaN/GaN‐based normally‐off GaN MOSFET with stress controlled 2DEG source and drain was proposed and fabricated using Al2O3 gate oxide deposited on the fully recessed gate region. The proposed normally‐off Al2O3/GaN MOSFET utilized AlGaN/GaN heterostructure source and drain with extremely high 2DEG density of 1.87×1014 cm2 with mobility of 120 cm2V‐1s‐1 and the device results were compared to those obtained from the reference device with normal AlGaN/GaN heterostructure source and drain with 2DEG density of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Compared with traditional GaN HEMTs, the gate voltage forward swing range increases more than 10 times and the reverse gate leakage is significantly suppressed for the GaN MOSHEMT. The forward breakdown voltage of gate junction of GaN MOSHEMT is V gs =22 V, and the reverse breakdown voltage is V gs =−90 V, the breakdown criterion being > ´-| | I 1 10 gs 5 A mm −1 . The MOS junction behaves like a Schottky junction with a barrier height of 1.1 V and the ideality factor is 2.5 after breakdown, which indicates that the breakdown of the junction is the breakdown of the gate dielectric.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with traditional GaN HEMTs, the gate voltage forward swing range increases more than 10 times and the reverse gate leakage is significantly suppressed for the GaN MOSHEMT. The forward breakdown voltage of gate junction of GaN MOSHEMT is V gs =22 V, and the reverse breakdown voltage is V gs =−90 V, the breakdown criterion being > ´-| | I 1 10 gs 5 A mm −1 . The MOS junction behaves like a Schottky junction with a barrier height of 1.1 V and the ideality factor is 2.5 after breakdown, which indicates that the breakdown of the junction is the breakdown of the gate dielectric.…”
Section: Resultsmentioning
confidence: 99%
“…Max Ids/mA•mm −1 Max Gm/mS•mm −1 Gate length/μm [5] 263, (Vgs=6 V, Vds=10 V) 72 0.25 [6] 230,(Vgs=10 V, Vds=7 V) 100 2 [7] 660, (Vgs=2 V, Vds=6 V) 250 1.4 This work 900, (Vgs=2 V, Vds=10 V) 250 0.5 Test results show that high current density, high tranconductance, negligible gate current, large gate voltage swing range and comparable RF characteristics of GaN MOSHEMT with traditional GaN HEMT have been obtained.…”
Section: Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…However, Ki-Sik et al and Zhe at al. reported that the electron transport characteristics could be seriously affected by the interface states in fully recessed HEMTs, due to the completely etched AlGaN barrier layer [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the field of semiconductor has seen tremendous technological and commercial progress, such as optoelectronic devices, 1,2) solar cells, 3) and high power electronic devices. 4) Otherwise, the research of GaN growth on Si substrate attracted extensive attentions because of its great potential in cost-effective industry applications. However, high quality GaN epilayer is hard to be obtained on Si substrate due to the existence of the large lattice mismatch and thermal expansion mismatch between GaN and Si.…”
Section: Introductionmentioning
confidence: 99%